MASTER SLAVE UNIT FOR VEHICLE TO EVERYTHING COMMUNICATION WITH GROUP KEY MANAGEMENT FOR TRAFFIC CONGESTION REDUCTION - Spandana Mande; Nandha Kumar Ramachandran (Proceedings on Engineering Sciences)
Information and communication technologies (ICT) provide innovative solutions for transportation, improving vehicle mobility with regard to security, reliability and quality. Intelligent Transportation Systems (ITS), which encompass Vehicle to Everything (V2X), utilize wireless connectivity to enhance road safety and operational efficiency. Although V2X and Vehicle-to-Vehicle (V2V) technologies improve traffic efficiency and safety, they also present security issues. V2V communication conveys road configuration and driver conduct information, necessitating certified V2X hardware and encrypted transmissions. Vehicular networks enhance traffic safety, disseminate accident information, and maximize efficiency. Due to the unpredictability of vehicular traffic, congestion presents a significant problem. The proposed research formulates a model for V2X communication among tollgates, establishing Vehicular Ad-Hoc Networks (VANETs) within a 200-meter radius. Vehicles fitted with sensor units maintain communication post-accident, thereby averting congestion. Data is encrypted with group keys, and a master-slave system guarantees precise transmission. This model enhances data rates and precision compared to conventional methods.